ANALISIS LIFE CYCLE ASSESSMENT (LCA) PROSES PERTAMBANGAN PERUSAHAAN SEMEN - Aulia Ulfah Farahdiba; Munawar Ali; Retno Kinanty Mistari (EnviroUS, 2022)
The demand for cement in Indonesia in the last 10 years has increased by 63%. One of the raw materials for making cement is obtained from mining activities, namely limestone and clay. The method used in this research is Life Cycle Assessment. .Life cycle assessment is used to conduct an environmental impact assessment and using a cradle to gate approach. The data for each processing process is analyzed using SimaPro software. The biggest impact contribution from LCA analysis on the mining process is Fine particulate matter formation and global warming (Human Health). The suggested alternative improvement program is air control or pollutant control by reforesting and developing green open spaces around the cement industrial area of Tuban Regency